Effects of Religiosity on Social Behaviour: Experimental Evidence from a Representative Sample of Spaniards - Pablo Bra\~nas-Garza; Antonio M. Espín; Shoshana Neuman (Institute for the Study of Labor (IZA), 2013)
This study explores the effect of several personal religion-related variables on social behaviour, using three paradigmatic economic games: the dictator (DG), ultimatum (UG), and trust (TG) games. A large carefully designed sample of a Spanish urban adult population (N=766) is employed. From participants' decisions in these games we obtain measures of altruism, bargaining behaviour and sense of fairness/equality, trust, and positive reciprocity. Three dimensions of religiosity are examined: (i) religious denomination; (ii) the intensity of religiosity, measured by active participation at church services; and (iii) converting out into a different denomination than the one raised in. The major results are: (i) individuals with no religion made decisions closer to rational selfish behaviour in the DG and the UG compared to those who affiliate with a standard religious denomination; (ii) among Catholics, intensity of religiosity is the key variable that affects social behaviour insofar as religiously-active individuals are generally more pro-social than non-active ones; and (iii) the religion raised in seems to have no effect on pro-sociality, beyond the effect of the current measures of religiosity. Importantly, behaviour in the TG is not predicted by any of the religion-related variables we analyse. Given the accelerating share of no religion individuals (in Europe and elsewhere) and the large influx of immigrants who tend to be more religiously active compared to the native populations our findings have significant implications for the future pro-sociality patterns in Europe.
Keywords: C7; C9; Z12; Z13; 330; church attendance; religion; economic experiments; pro-social behaviour; Spain; Soziales Verhalten; Religion; Spieltheorie; Test; Spanien